Drosophila oncogene Gas41 is an RNA interference modulator that intersects heterochromatin and the small interfering RNA pathway. (17th November 2014) - Gandhi, Sumit G.; Bag, Indira; Sengupta, Saswati; Pal‐Bhadra, Manika; Bhadra, Utpal
<x xml:space="preserve">Abstract</x> Glioma amplified sequence41 (Gas41) is a highly conserved putative transcription factor that is frequently abundant in human gliomas. Gas41 shows oncogenic activity by promoting cell growth and viability. In the present study, we show that Gas41 is required for proper functioning of RNA interference (RNAi) machinery in the nuclei, although three basic structural domains of RNAi components PAZ, PIWI and dsRNA with respect to binding are absent in the structural sequences. Variations of structural domains are highly conserved among prokaryotes and eukaryotes. Gas41 interacts with cytological RNase III enzyme Dicer1 both biochemically and genetically. However, Drosophila Gas41 functions as chromatin remodeler and interacts with different heterochromatin markers and repeat‐induced transgene silencing by modulating position effect variegation. We also show that transcriptional inactive Gas41 mutant interferes with the functional assembly of heterochromatin‐associated proteins, dimethylated lysine 9 of histone H3 and heterochromatic protein 1 in developing embryos. A reduction of heterochromatic markers is accompanied by the mini‐w promoter sequence in Gas41 mutants. These findings suggest that Drosophila Gas41 guides the repeat associated gene silencing and the Dicer1 interaction, thereby depicting a new role for Gas41. Gas41 is a critical RNAi component. In Drosophila, Gas41 plays a dual role. On the one hand, it appears to participate with Dicer 1 in the RNAi pathway and, alternatively, it also participates in repeat‐induced gene silencing by accumulating heterochromatin proteins at the mini‐w array promoters. Therefore, it represents an intriguing and apparently paradoxical new finding in RNA technology with respect to the process of heterochromatin gene silencing.